To what extent is it right to measure serum vaspin, obestatin, and apelin-36 levels without a protease inhibitor in nonalcoholic fatty liver disease? - Aydin, Suleyman; Sahin, Ibrahim; Demirel, Ulvi; Aksoy, Aziz (My University, 2011)
[Abstract Not Available]
Keywords: Fatty Liver; Ghrelin; Humans; Intercellular Signaling Peptides and Proteins; Protease Inhibitors; Serpins; amino acid; apelin; apelin 36; aprotinin; benzylsulfonyl fluoride; caspase; gamma glutamyltransferase; kallikrein inhibitor; obestatin; proteinase inhibitor; unclassified drug; vaspin; apoptosis; biochemistry; blood analysis; disease course; gamma glutamyl transferase blood level; gastrointestinal tract; hormone blood level; human; letter; liver cirrhosis; nonalcoholic fatty liver; priority journal; protein degradation; tube